Spatial Differences and Influencing Factors of Urban Water Utilization Efficiency in China - Liu, Kai; Liu, Wenrui; Wu, Jialing; Chen, Zhongfei; Zhang, Wen; Liu, Fang (Frontiers in Environmental Science, 2022)
The purpose of urban water management is to improve urban water utilization efficiency (UWUE), which in turn addresses water shortages in urban areas. The present study aimed to evaluate the UWUE of 284 cities at the prefecture level in China between 2003 and 2018 by the slacks-based measure of super-efficiency, explore its spatial differences through exploratory spatial data analysis, and analyze the influencing factors using the statistical tool Geodetector. The results showed that the average value of UWUE in China was generally low but tended to rise gradually. There were significant spatial differences in UWUE across China, with considerable global and local spatial autocorrelation, and local spatial autocorrelation was characterized primarily by high-high and low-low regions. Industrial structure and urban population were the main influencing factors for UWUE. Finally, based on these findings, we offered policy implications for improving UWUE and coordinated development between cities.